The role of Great Recession on income polarization by population groups - Chiara Assunta Ricci; Sergio Scicchitano (Global Labor Organization (GLO), 2021)
In this paper we use two different non-parametric methods to disentangle the role of Great Recession on income polarization in Italy by population groups (gender, occupational status, education, age, residential area and state of birth). By using data from the Survey on Household Income and Wealth of the Bank of Italy, first, we decompose the Duclos, Esteban and Ray polarization index by population groups. Second, we employ the Relative Distribution Approach by groups. Our results show a general downgrading, particularly of lower incomes, where low-educated, young, southern and foreign head of household are located out of the crisis. Young people and especially foreigners have suffered the most from the crisis. The lowest (highest) homogeneity within groups and the lowest (highest) heterogeneity between groups is observed when groups are formed on the basis of the state of birth (residential area).Thus, the decomposition of the polarization indices by population groups is able to provide specific useful policy indications, tailored to groups' needs.
Keywords: D3; J3; C14; 330; Polarization; Non-parametric method; Decomposition; Relative distribution; Income distribution; Great Recession